Effect Of Compound Training According To Training Progression In Intensity On Some Physical Abilities And High Jump Scoring Accuracy In Handball Among Young Players - Dhurgham Abd Baqir; Asaad Flaih Hasan (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Sports training is a structured educational process based on scientific principles, aimed at preparing athletes according to their varying levels and capabilities. It strives for continuous improvement of their physical and technical skills to achieve peak performance in their chosen activity or specialized skill. Physical conditioning is a cornerstone of this process, playing a vital role in supporting gradual development of performance in accordance with demands of game and individual differences among players. Handball is characterized by a fast pace and constant changes between defense and attack, requiring development of several physical and motor skills that influence offensive performance, particularly skill of shooting from a high jump. Through field observations by the researcher while supervising training of local teams, it became clear that most clubs focus on specific preparation phase without adopting integrated training units that combine strength, speed, skill, and endurance in a progressive and comprehensive manner. This approach fails to achieve a scientifically sound increase in training load, reduce signs of fatigue, and contribute to optimal physical and technical adaptation. research aims to identify effect of compound training based on gradual increase in training load intensity on some physical abilities and accuracy of high jump shooting skill among handball players. the researcher started from hypothesis that there are statistically significant differences between results of pre- and post-tests of research sample. To achieve study’s objectives, the researcher employed an experimental approach using a single experimental group. research sample consisted of six youth handball players from Al-Shatra Club. results demonstrated that integration of physical and technical aspects contributed to improved coordination and motor skills, facilitating transfer of physical training to technical performance during shooting. Based on these findings, the researcher recommended adopting a combined training program supported by diverse training methods and progressively increasing intensity, tailored to movement patterns of high jump shooting skill.